Persepsi dan Perilaku Pengguna dalam Menggunakan Aplikasi Mobile Gojek untuk Pemesanan Makanan Secara Online: Persepsi Kemudahan Penggunaan, Persepsi Kegunaan, Pengalaman Pengguna dan Kepuasan Pengguna - Monika Silvia Gultom; Mariana Simanjuntak (Pusat Riset dan Inovasi Nasional, 2024)
Mobile applications have become an integral part of everyday life. One example is Gojek, which is popular in Indonesia with a variety of services including online food ordering. Ordering food through this application offers comfort and convenience for users. To gain a deeper understanding of user responses and behavior in using this application, comprehensive research is needed. The method used in this research uses a quantitative approach. The results of this research are that User Satisfaction (KP) has an R-Square value of 0.699 and an Adjusted R-Square value of 0.666. Then the User Experience (PP) variable has an R-Square value of 0.402 and an Adjusted R-Square value of 0.382. This means that the User Satisfaction (KP) variable contributes 69.9%, the remaining 30.1% is caused by variables that have not been studied. Furthermore, the User Experience (PP) variable contributed 40.2%, the remaining 59.8% was caused by variables that had not been studied.